The beginning of football infrastructure development in Lviv and Kharkiv: common and.different in the knowledge to this branch of sport (late XIX – early XX century) - Mykolenko, Dmytro (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
Infrastructure is one of the main components of football industry today. Grounds, sports complexes and stadiums with stands for spectators, sporting goods stores, museums of various teams and clubs are important. These buildings began to appear in Central-Eastern Europe in the late ХІХ and early ХХ centuries. Purpose. The purpose of this study is comparison of knowledge transfer about football infrastructure in Lviv and Kharkiv. Research methodology. We understand concept of "transfer of knowledge" as a transfer of technologies developed in Western Europe to the football infrastructure of Lviv and Kharkiv with their implementation in the construction of appropriate sports facilities.Scientific novelty. In this work, for the first time, we made to compare the process of knowledge transfer about football infrastructure in two non-port cities – Lviv and Kharkiv, which were part of two different empires – Austria-Hungary and Russia. This makes it possible to clarify the factors that determined the specifics of the specified process, as well as to establish common features of the dissemination of information about the rules for arranging stadiums and football fields.Conclusions. In the largest city of Slobozhanshchyna, foreigners who worked at one of the factories created football ground. British and Belgians used his knowledge that they had received in their homeland. Even then, Kharkiv football fans used it as example for building their own playgrounds. In Lviv, the initiative to start sports infrastructure belonged to local residents. They were represented by sports clubs and educational institutions. An important way to spread knowledge about the development of football infrastructure in Lviv was the publication of brochures on this topic. In the late ХІХ – early ХХ century they were published in Polish and Ukrainian. We don’t see these practices in Kharkiv.